Trace and Rare Earth Element (REE) Geochemistry of Recently Formed Stromatolites at Lake Salda, SW Turkey - Kaya, Mustafa; Yildirim, Belgin Aydin; Kumral, Mustafa; Sasmaz, Ahmet (Mdpi, 2023)
Stromatolites are the oldest recognized fossil recordings of life on Earth. Therefore, their study of them represents one of the most interesting topic that investigates the physio-chemical environmental conditions (formations and precipitations) at which the stromatolites formed. This work deals with the rare earth elements (REEs) geochemical characteristics and the redox-sensitive trace elements behavior of the stromatolites newly formed in Salda Lake, a closed system alkaline lake surrounded by serpentinite rocks in SW Turkey. The representative stromatolite samples collected from Salda Lake show higher contents of MgO (up to 41.5 wt.%), CO2+OH (up to 56.6 wt.%), and MgO/CaO ratio (up to 42.2 wt.%) referring to the stromatolites had been controlled by microorganisms and deposited in subtidal areas having hydro-magnesite and aragonite mineralogy. The average trace element contents of the stromatolites are 8.4 ppm V, 0.09 ppm Cr, 3.50 ppm Co, 95.6 ppm Ni, 0.73 ppm Cu, 1.55 ppm Rb, 37.6 ppm Sr, 0.59 ppm Y, 17.7 ppm Zr, 3.60 ppm Nb, 21 ppm Ba, 0.05 ppm Hf, 3.5 ppm As, 0.02 ppm Cd, 0.05 ppm U, 0.05 ppm Th, 2.85 ppm Pb, and 6.60 ppm Zn. The Post-Archean Australian Shale (PAAS)-normalized REE patterns of the stromatolites reveal that the heavy REEs (HREEs) are enriched relative to the light REEs (LREEs) with highly negative Y and Ce-anomalies and positive Eu-anomalies. This refers to the stromatolites formed in predominantly oxidizing environmental conditions at partially warm lake waters. In addition, the hydromagnesite composition of the Salda Lake stromatolites indicates that they were precipitated from the waters influenced by Mg-rich meteoric waters fed from the serpentinite rocks around the Lake.
Keywords: rare earth element (REE) geochemistry; stromatolites; Lake Salda; SW Turkey